Rekonstruksi Pemilu Perspektif Hukum Tatanegara Islam: (Antara Legitimasi Demokrasi dan Substansi Syariah) - Fiantika Armanda; Salsa Luthfiah Rezki; Raisya Aurora A; Kurniati Kurniati (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2026)
Elections are the primary instrument in a democratic system, functioning as a means to realize popular sovereignty and legitimize political authority. However, election implementation in Indonesia continues to face several challenges, including money politics, elite domination, low-quality political participation, and democratic practices that tend to emphasize procedural aspects rather than substantive justice. This study aims to analyze electoral reconstruction from the perspective of Islamic constitutional law, focusing on its opportunities, challenges, and implications for improving the quality of democracy in Indonesia. The research uses a normative legal method with conceptual and literature-based approaches by examining relevant legal sources and scholarly works. The findings show that electoral reconstruction can be carried out by strengthening the principles of shura, trustworthiness, justice, public participation, transparency, and accountability in election management. This reconstruction offers considerable opportunities because Islamic constitutional values are generally consistent with democratic principles. Nevertheless, its implementation faces obstacles such as pragmatic political culture, elite dominance, money politics, and limited public political awareness. Overall, electoral reconstruction based on Islamic constitutional values can improve democratic quality, strengthen electoral integrity, and promote a more just political system oriented toward public welfare.